Seroprevalence to Rabies Virus in Wildlife in Brazil - Fornazari, Felipe [UNESP]; Scheffer, Karin Corrêa; Dos Ramos Silva, Sandriana; da Silva, Karina Ribeiro; Rodrigues, Adriana Cândido; Teixeira, Carlos Roberto [UNESP]; Rolim, Luna Scarpari [UNESP]; Langoni, Helio [UNESP] (Wildlife Disease Association, 2022)
Serum samples of 638 free-ranging wild mammals from São Paulo state, Brazil, were tested for neutralizing antibodies against rabies virus by the rapid fluorescent focus inhibition test. Overall seroprevalence was 1.7% among 24 species surveyed, with individuals of six species having positive results indicating exposure to rabies virus.